1982
DOI: 10.1002/pol.1982.180201014
|View full text |Cite
|
Sign up to set email alerts
|

Phase behavior of the quasiternary system N‐methylmorpholine‐N‐oxide, water, and cellulose

Abstract: The crystallization and melting behavior of the system N‐methylmorpholine‐N‐oxide (MMNO)–H2O–cellulose has been studied by differential scanning calorimetry, optical and electron microscopy, and x‐ray scattering. The phase diagram of the MMNO–H2O solvent system is reported up to a water content of 28% w/w. MMNO forms two crystalline hydrates, namely a monohydrate (13,3% w/w H2O) and a hydrate comprising five molecules of crystal water per two MMNO molecules (28% w/w H2O), which melts at 78°C and 39°C, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 14 publications
4
81
1
Order By: Relevance
“…Simulation systems were prepared analogously to the dilute solutions: For TMAO/water, 600 molecules were used at 1 bar and a temperature of 533.15 K, above the melting point of the amorphous monohydrate of 474.15 K as reported by Hattori. 59 For the NMMO/water mixtures, 440 molecules were simulated at 1 bar and 373.15 K, the temperature used in industrial cellulose processing, also above the experimental melting point of 345.15 K. 2 The sampling time was 300 ps for each system. In contrast to the dilute solutions, we observe in the equimolar case a rather strong dependence on the chosen model, more visible for TMAO: The average density from the partly rigid model is 0.672 g cm -3 , and for the fully flexible one, it is 0.764 g cm -3 .…”
Section: Molecular Dynamics Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation systems were prepared analogously to the dilute solutions: For TMAO/water, 600 molecules were used at 1 bar and a temperature of 533.15 K, above the melting point of the amorphous monohydrate of 474.15 K as reported by Hattori. 59 For the NMMO/water mixtures, 440 molecules were simulated at 1 bar and 373.15 K, the temperature used in industrial cellulose processing, also above the experimental melting point of 345.15 K. 2 The sampling time was 300 ps for each system. In contrast to the dilute solutions, we observe in the equimolar case a rather strong dependence on the chosen model, more visible for TMAO: The average density from the partly rigid model is 0.672 g cm -3 , and for the fully flexible one, it is 0.764 g cm -3 .…”
Section: Molecular Dynamics Simulation Resultsmentioning
confidence: 99%
“…Furthermore, the biochemical relevance of dissolved compounds in water is an important aspect of current research on protein stability and biomolecular recognition. Tertiary aliphatic Noxides are remarkable species in these respects: Some are known as good cosolvents with water for dissolving cellulose fibers, [1][2][3][4][5][6] increasing the reactivity of the swollen cellulose material for further derivatization in pollution-free industrial fiber processing. For instance, N-methylmorpholine-N-oxide (NMMO) in water dissolves cellulose, whereas N,N,N-trimethylamine-N-oxide (TMAO) does not.…”
Section: Introductionmentioning
confidence: 99%
“…Fink et al (2001) has reviewed the structure formation of regenerated cellulose materials from NMMO solutions. A study by Chanzy et al (1982) revealed that the reaction is favored by the formation of hydrogen bonds between the oxygen of the strong N-O dipoles in NMMO with other compounds containing hydroxyl groups, such as water, alcohol, and cellulose. However, water and cellulose will compete with each other to bind with NMMO molecules, which seem to prefer water.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Similar to polypeptides and DNA, cellulose can form cholesteric LC phases. 33 Werbowyj and Gray 34 first reported the cholesteric phase of aqueous hydroxypropyl cellulose in 1976. Since then, the LC behaviors of cellulose derivatives have aroused much interest in LC polymers within the scientific community.…”
Section: Introductionmentioning
confidence: 99%